Rider Haggard and the imperial occult : hermetic discourse and Romantic contiguity - Magus, Simon (Aries book series, 2022)
"This book critically examines the literary oeuvre of H. Rider Haggard, placing it in the nineteenth- century occult milieu in which he wrote, and from which he took ideas which remained with him into the first decades of the twentieth century. Building upon earlier trajectories of Haggard studies, notably postcolonialist, psychoanalytic, and feminist platforms, it critiques and nuances these whilst taking a novel approach in elucidating the religio- philosophical and esoteric ideas which are prolific in his work"--